2015
DOI: 10.1108/ijssp-02-2014-0010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between organizational commitments and organizational citizenship behaviour in a sample of private banking employees

Abstract: Purpose – The purpose of this paper is to investigate whether there was a relationship between commitment and the behaviour of organizational citizenship among bank employees. Design/methodology/approach – This paper is based on the outcomes of a doctoral dissertation, which was a case study combining a mix methodology. The results validated the conceptual model proposed by the researcher and answered the research questions. Measurement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
50
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 34 publications
6
50
0
7
Order By: Relevance
“…Therefore, affective commitment among bank employees is very important in order to boost their satisfaction so that they will stay with their organization. On the other hand, Zayas-Ortiz et al (2015) discovered that many banking organizations are sensitive to the concepts of fairness and justice in developing mechanisms to ensure that employees perceive that they are treated fairly. Employees who recognize justice and equity through the distribution of tasks and work processes are more likely to develop a high degree of affective commitment.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, affective commitment among bank employees is very important in order to boost their satisfaction so that they will stay with their organization. On the other hand, Zayas-Ortiz et al (2015) discovered that many banking organizations are sensitive to the concepts of fairness and justice in developing mechanisms to ensure that employees perceive that they are treated fairly. Employees who recognize justice and equity through the distribution of tasks and work processes are more likely to develop a high degree of affective commitment.…”
Section: Problem Statementmentioning
confidence: 99%
“…Based on the views from Zayas-Ortiz et al (2015) it can be concluded that research concerning bank employees' affective commitment towards their organization especially with regard to issues of organizational justicein the Malaysian banking industry is crucial and important primarily due to the lack of extant literatures. Greenberg and Baron (2003) defined distributive justice as employees' perceptions of fairness in the distribution of resources between people.…”
Section: Problem Statementmentioning
confidence: 99%
“…Dalam memaksimalkan potensi karyawan dalam suatu perusahaan, karyawan haruslah memiliki loyalitas kerja yang tinggi karena, jika karyawan sudah loyal terhadap perusahaan, maka karyawan tersebut akan sukarela bekerja pada perusahaannya (Yu et al, 2015). Hal yang menyebabkan kurangnya loyalitas karyawan adalah kurang perhatian pimpinan terhadap bawahan, pembayaran pekerjaan itu sendiri, promosi yang akan didapatkan, atasan ditempat kerja dan juga rekan-rekan sesama karyawan yang dapat menciptakan kenyamanan tinggi bagi karyawan tentu yang dapat berpengaruh terhadap keseriusan karyawan dalam bekerja (Zayas-ortiz et al, 2015).…”
Section: Pendahuluanunclassified
“…Due to its importance, strategies and tools such as organizational citizenship behavior (OCB), customer orientation behavior (COB) and etc. has been put in place to ensure efficient and effective enhancement of employee attitude towards service delivery behavior (Lin & Lin, 2011;Mechinda & Patterson, 2011;Jain, 2015;Zayas-Ortiz, Rosario, Marquez, & Gruneiro, 2015;Wen, Li & Hon, 2016;Chumg, Seaton, Cook & Ding, 2016). Its influence within any service organization culminates in either positive or negative reputation (Echchakoui, 2016); accomplished or unaccomplished goals as well as commitment or lack of commitment, thereof (Ratanavaraha, Jomnonkwao, Khampirat, Watthanaklang, & Iamtrakul, 2016, Verbich, & Ahmed, 2016.…”
Section: Introductionmentioning
confidence: 99%